1971
DOI: 10.1111/j.1529-8817.1971.tb01481.x
|View full text |Cite
|
Sign up to set email alerts
|

SPHEROPLAST FORMATION AND ASSOCIATED ULTRASTRUCTURAL CHANGES IN A SYNCHRONOUS CULTURE OFANACYSTIS NIDULANSTREATED WITH LYSOZYME1,2

Abstract: SUMMARY Cells of Anacystis nidnlans were grown in synchronous culture using a light‐dark alternation to obtain synchronization. Two synchronous cycles were obtained with, decay of synchrony beginning with the third cycle. Cells of various ages in the growth cycle were treated with lysozyme to form spheroplasts. The percentage of spheroplast formation varied with age of the cells. After extended periods of lysozyme treatment, up to 90% of the cells of all ages showed spheroplast formation. Some cells were resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…This fact is due to the higher recovery of biocomponents with Alcalase ® than with the control and other enzyme extractions ( Figure 5A,B). These observations agree with previous studies, where cyanobacteria cells modified their shape and size, swelling after a Lysozyme treatment [32]. Less cellular material remained in the residual biomasses extracted with Ultraflo ® and Vinoflow ® ( Figure 5C,D) than in the control experiment (lower observed electronic density).…”
Section: Biomass Analyses By Temsupporting
confidence: 92%
“…This fact is due to the higher recovery of biocomponents with Alcalase ® than with the control and other enzyme extractions ( Figure 5A,B). These observations agree with previous studies, where cyanobacteria cells modified their shape and size, swelling after a Lysozyme treatment [32]. Less cellular material remained in the residual biomasses extracted with Ultraflo ® and Vinoflow ® ( Figure 5C,D) than in the control experiment (lower observed electronic density).…”
Section: Biomass Analyses By Temsupporting
confidence: 92%
“…1), this correlation may not be causal. However, although lysozyme causes some changes in the ultrastructure of A. nidulans, no such changes were reported in cells of a control in mannitol without lysozyme (6). Further, we have observed no inhibition of dark respiration in Anacystis and Coccochloris after mannitol treatment.…”
contrasting
confidence: 69%
“…We attribute the increase in rate of ferricyanide reduction to increase in permeability of the cell wall/membrane barriers. The term permeaplast provides a functional rather than a morphological description, although the cells appear more closely related to "spheroplasts" than to "protoplasts," since electron microscopy has shown that at least one cell wall layer remains (9).…”
Section: Discussionmentioning
confidence: 99%